A Highly Fluorinated Chiral Aldehyde for Enantioselective Fluorescent Recognition in a Biphasic System. Issue 45 (26th July 2017) - Wang, Chao; Wu, Xuedan; Pu, Lin
Abstract: A 1, 1′‐bi‐2‐naphthol (BINOL)‐based aldehyde containing four perfluoroalkyl groups has been designed and synthesized. It shows enantioselective fluorescence enhancement at 420 nm when treated with the enantiomers of trans ‐1, 2‐diaminocyclohexane in an organic/fluorous biphasic system. The enantiomeric excess of the diamine in methanol can be linearly correlated with the emission intensity of of the aldehyde in perfluorohexane (FC‐72). This is the first example to determine the enantiomeric composition of a chiral molecule by using a fluorescent sensor in a fluorous/organic biphasic system. The mechanism of the reaction was investigated by NMR spectroscopy and mass spectrometry. Abstract : A highly fluorinated molecular probe can selectively extract one enantiomer of a chiral diamine from a methanol solution into a fluorous phase to show enantioselective fluorescent enhancement.